To Study the Effect of Oil Palm Empty Fruit Bunch (OPEFB) Fibre Ratio on The Mechanical Properties of EFB Cement Board for Panelling - Izzah Basiran; Ja’afar, Azman (Progress in Engineering Application and Technology, 2022)
Oil Palm Empty Fruit Bunch (OPEFB) is one of the biomasses produced in oil palm agriculture. It is important to acknowledge the physical and mechanical properties of the EFB before being utilised in the suitability of fabrication of the cement-fibre board. However, there are compatibility issues within the EFB fibre with the cement mixtures. This is because fibres contain residual oil and sugar that prevent cement setting and its hydration. Also, the cell chemical of fibre has been said to be the factor that influences the physical and mechanical properties of cement board fibre. Thus, this study was directed to perform the compatibility assessments in order to improve the cement board fibre mixture. The fabrication of cement board fibre samples was done by incorporating pretreatment of 4% NaOH concentration EFB having different percentage ratios which are 5%, 7%, 10% and 12% to be able to find the effect of fibre percentage ratio on cement fibre board. The test sample performed to measure the mechanical and physical properties were Modulus of Elasticity (MOE), Modulus of Rupture (MOR), compression strength test, density, Thickness Swelling (TS), and water absorption. The results showed that EFB fibre affected the mechanical and physical properties of the cement board after it had gone through the tests. The optimum weight percentage of EFB fibre ratio is when the result from the test achieved BS EN standard.